2015
DOI: 10.1021/acs.jpcc.5b00691
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cluster–Support Interactions on Reactivity of Size-Selected NbxOy Clusters

Abstract: Size-selected niobium oxide nanoclusters (Nb 3 O 5 , Nb 3 O 7 , Nb 4 O 7 , and Nb 4 O 10 ) were deposited at room temperature onto a Cu(111) surface and a thin film of Cu 2 O on Cu(111), and their interfacial electronic interactions and reactivity toward water dissociation were examined. These clusters were specifically chosen to elucidate the effects of the oxidation state of the metal centers; Nb 3 O 5 and Nb 4 O 7 are the reduced counterparts of Nb 3 O 7 and Nb 4 O 10 , respectively. From twophoton photoemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 89 publications
4
43
0
Order By: Relevance
“…S7). These features shift to lower binding energies when the Nb 5.0 -β sample has been treated with H 2 O 2 (details given in section 2.4).Figure 4bshows that XPS spectra of H 2 O 2 -activated Nb 5.0 -β contains overlapping doublet features with doublets at 210.6 and 208.0 eV as well as at 209.7 and 207.0 eV, which resemble reported values for Nb V and Nb IVspecies[72],[73], and is consistent with the presence of the proposed Nb V -(O 2 ) and Nb IV -(O 2 ) species, respectively. Under ultra-high vacuum conditions (i.e., 10 -9 Torr), the preferred state of the H 2 O 2 -activated Nb-β is Nb IV -(O 2 ), because the lack of free protons favors the formation of the superoxo species, as shown for H 2 O 2 -activated TS-, which explains why the magnitude of the features for Nb IV is much larger than for Nb V on H 2 O 2 -treated materials.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…S7). These features shift to lower binding energies when the Nb 5.0 -β sample has been treated with H 2 O 2 (details given in section 2.4).Figure 4bshows that XPS spectra of H 2 O 2 -activated Nb 5.0 -β contains overlapping doublet features with doublets at 210.6 and 208.0 eV as well as at 209.7 and 207.0 eV, which resemble reported values for Nb V and Nb IVspecies[72],[73], and is consistent with the presence of the proposed Nb V -(O 2 ) and Nb IV -(O 2 ) species, respectively. Under ultra-high vacuum conditions (i.e., 10 -9 Torr), the preferred state of the H 2 O 2 -activated Nb-β is Nb IV -(O 2 ), because the lack of free protons favors the formation of the superoxo species, as shown for H 2 O 2 -activated TS-, which explains why the magnitude of the features for Nb IV is much larger than for Nb V on H 2 O 2 -treated materials.…”
supporting
confidence: 62%
“…X-ray photoelectron spectroscopy (XPS) was used to determine the oxidation state of Nb in both untreated and H 2 O 2 -activated (Section 2.4) Nb 5.0 -β samples in order to verify the presence of Nb IV species (i.e., Nb IV -(O 2 )). Figure 4a shows the XPS spectra for untreated Nb 5.0 -β in the Nb 3d region (200 -220 eV), which possesses a doublet with absorbance peaks centered at 210.6and 208.0 eV that correspond to Nb V 3d 3/2 and 3d 5/2 , respectively[72,73] (fitting that demonstrates the absence of Nb IV is provided in the SI,Fig. S7).…”
mentioning
confidence: 99%
“…[23][24] We have recently shown that surface dipole moments derived from coverage-dependent work function shifts of metal oxide clusters deposited on a metal surface can be used to probe the electron transfer between the cluster and metal support. [25][26] The surfaces in these studies were prepared by depositing size-selected M x O y clusters (M = Mo, W, Ti, Nb) onto a Cu(111) surface as model "inverse" catalysts for the WGSR. Inverse models of WGSR catalysts have helped clarify the role of the metal oxide, and for Cu-ceria catalysts, the inverse CeO x /Cu(111) system is more reactive than the conventional ceria supported Cu catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…13-14, 31, 36-39 The measured surface dipoles for the oxide clusters deposited on Cu(111) were found to be consistent with Cuoxide cluster electron transfer, the extent of which roughly correlated with the bulk work function of the metal oxide (stoichiometric and reduced) and also the metal-to-oxygen stoichiometry of the cluster. [25][26] Temperature programmed reaction studies show that electron transfer alone, however, is a poor predictor of water dissociation activity. For example, Mo 3 O 9 on Cu(111) exhibits a large surface dipole ( = -2.8 D) and no detectable water dissociation, whereas both substoichiometric Nb 3 O 5 ( = -0.4 D) and stoichiometric Nb 4 O 10 ( = -2.1 D) clusters on Cu(111) are active for water dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of ions without their counterions from the gas phase is enabled by ion soft landing, a technique first introduced by Cooks and coworkers 11 , which enables immobilization of ions of one polarity on a support. Soft landing has been used previously for conformational enrichment of peptides 12 , understanding protein folding on surfaces 13 , 14 , deposition of intact protein assemblies for microscopic imaging 15 , generation of microarrays for biological screening 16 , preparation of well-defined model catalysts through deposition of ionic clusters, nanoparticles and organometallics 17 23 and in material sciences (e.g., thin composite materials 24 and processing of graphene 25 ). In these studies, relatively low coverage samples were prepared for characterization and surface science experiments 26 .…”
Section: Introductionmentioning
confidence: 99%